Determining factors of discrimination towards latinamerican immigrants in northern Chile (Revista Iberoamericana de Estudios Municipales, 2023)
The objective of this research is to analyze the determining factors of discrimination of Latin American immigration in a region in the northern part of Chile, the Atacama region. The research is descriptive and a non-probabilistic sample of 88 immigrants was analyzed using a set of socioeconomic variables such as: The most mentioned type of discrimination is employment discrimination (21.6%), followed by gender discrimination. racism or xenophobia (17.3%) and, in third place, discrimination due to language use (13.5%). The chi-square distribution analysis allowed us to verify that women are more discriminated against than men and that the level of education does not influence discrimination.
Keywords: inmigration; discrimination; descriptive analysis